2017
DOI: 10.21448/ijsm.356250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt Stress on Seed Germination, Shoot and Root Length in Basil (Ocimum basilicum)

Abstract: Salinity is one of the most environmental problems in arid and semi-arid region. It is an abiotic stress factor which restricts crop production and affects development of plants. One of the these plants is basil (Ocimum basilicum). It is an annual medicinal and aromatic plant from Lamiaceae family. The present study was carried out to determine the response of different salt concentrations from 0 to 240 mM doses which increasing 20 mM. The experiment was conducted with randomized complete block design with 3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The ADB was significantly correlated with TDW and LA ( p < 001). The germination potential was positively correlated with germination rate, shoot length, and root length under salt stress ( p < 0.05), in accordance with the previous studies ( Taghvaei et al, 2012 ; Amlca and Yaldz, 2017 ). Our findings revealed that the traits of germination were not significantly correlated with the seedling traits, suggesting that the regulatory mechanism of salt stress responses was likely to be different between the germination and seedling stages.…”
Section: Discussionsupporting
confidence: 92%
“…The ADB was significantly correlated with TDW and LA ( p < 001). The germination potential was positively correlated with germination rate, shoot length, and root length under salt stress ( p < 0.05), in accordance with the previous studies ( Taghvaei et al, 2012 ; Amlca and Yaldz, 2017 ). Our findings revealed that the traits of germination were not significantly correlated with the seedling traits, suggesting that the regulatory mechanism of salt stress responses was likely to be different between the germination and seedling stages.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Gholizadeh et al (2016) reported that flax seeds were more tolerant to salt stress than echinacea and artichoke seeds during the germination period. Similarly, Çamlıca and Yaldız (2017) reported that NaCl significantly affected basil seed germination, shoot and root length. On the other hand, the highest germination percentage, and the highest root length were found under control condition.…”
Section: Discussionmentioning
confidence: 90%
“…Increased RL as compared to SL may lead to the preservation of a large proportion of toxic ions in the roots and ameliorate their movement to the shoot, thus helping plant survival under salt stress ( Cassaniti et al, 2009 ; Cassaniti et al, 2012 ). Çamlıca and Yaldız (2017) reported a decreased root/shoot length ratio with increasing salinity doses, with a greater reduction in root length than shoot length. In other words, the root length was more negatively affected than shoot length by increasing salinity doses.…”
Section: Discussionmentioning
confidence: 95%